Answer:
C; right answer on Khan Academy
Step-by-step explanation:
Answer:
Can you show the full problem so that I can help
The answer is: x² – 6x + 9 = 0 .
_____________________________________________________
Explanation:
________________________________________________________
Given: (x – 3)² = 0 ; write as: general form: "ax² + bx + c = 0"; a ≠ 0 .
<span>
Note: </span>(x – 3)² = (x – 3)(x – 3) = x² – 3x – 3x + 9 = x² – 6x + 9 ;
___________________________________________________
Rewrite: (x – 3)² = 0 ; →
as: x² – 6x + 9 = 0 ; which is our answer.
____________________________________________
→ x² – 6x + 9 = 0 ; is in "general form", or "standard equation format"; that is: " ax² + bx + c = 0 "; (a ≠ 0) ;
→ in which:
a = 1 (implied coefficient, since anything multiplied by "1" is that same value);
b = -6;
c = 9
_______________________________________________________
Answer:
$448
Step-by-step explanation:
First, converting R percent to r a decimal
r = R/100 = 7%/100 = 0.07 per year,
then, solving our equation
I = 3200 × 0.07 × 2 = 448
I = $ 448.00
USE THE EQUATION Interest= Principal x rate x time
0.270 repeated. I used long division and a calculator. hoped this helped.